The Influence of the Geographical Inquiry Learning Model on the Ability to Solve Spatial Problems on Erosion Problems - Fitah, Alqurani Aliyu; Purwanto (CV Bumi Spasial, 2026)
The erosion problem in the upper Brantas watershed is closely linked to land-use change and increasing economic pressure on local communities, making it a relevant topic in Geography learning. However, Geography instruction at Panjura Malang High School remains largely theoretical, limiting students’ ability to critically analyze environmental problems and spatial phenomena. To address this issue, this study adopts the spatial thinking framework proposed by the National Research Council 2006, which defines spatial problem-solving as a cognitive process integrating spatial concepts, representational tools, and reasoning processes. Based on this framework, the study examines the effect of the Geographical Inquiry learning model on students’ ability to analyze erosion-related spatial phenomena. A quasi-experimental method with a pretest–posttest control group design was applied to two XI IPS classes selected through purposive sampling over four weeks, consisting of eight learning sessions of 2 × 45 minutes. Data were collected through classroom observations and validated essay tests. Independent sample t-test analysis using SPSS showed a significant difference between the experimental and control groups (t(38) = 2.212; p = 0.033), with higher post-test scores achieved by the experimental group. Simple regression analysis also indicated that the Geographical Inquiry model significantly improved students’ spatial problem-solving ability (F(1,18) = 5.181; p = 0.035). These results suggest that the Geographical Inquiry model is an effective alternative learning strategy for improving spatial problem-solving skills, although its implementation requires adequate spatial data and active teacher guidance.